Delayed reactions to drugs show levels of perforin, granzyme B, and Fas-L to be related to disease severity. - Posadas, Sinforiano Jose; Padial, Antonia; Torres-Jaén, María Josefa; Mayorga Mayorga, Cristobalina; Leyva-Fernández, Laura; Sánchez, Elena; Álvarez, Javier; Romano, Antonino; Juárez, Carlos; Blanca, Miguel; Sánchez, Elena (Elsevier, 2002)
Background Drugs can induce different immunologic reactions; T-cell mediated responses produce the most severe reactions. Although in vitro studies show that T cells recognize drugs or their metabolites and induce an effector cytotoxic response, direct in vivo evidence of involvement is lacking. T lymphocytes produce cytotoxic markers that are responsible for 2 major pathways to cell death: granule-mediated exocytosis (perforin and granzyme B) and Fas/FasL interaction. Objective: The purpose of this investigation was to establish the role of proinflammatory TNF-α and cytotoxic markers in subjects with delayed responses to drugs. Methods: We assessed expression levels by quantitative-competitive PCR of TNF-α, perforin, granzyme B, and FasL in mononuclear cells from peripheral blood and blister fluid from subjects with delayed reactions to drugs. Samples were obtained within 24 hours of the reaction and 30 days later. Fifteen patients were included and classified according to severity of the reaction, as follows: (A) maculopapular exanthema, (B) desquamative exanthema, (C) Stevens-Johnson syndrome, (D) toxic epidermal necrolysis. Results: At the acute stage, there was a large increase in TNF-α (9-fold), perforin (6-fold), and GrB (7-fold) in patients in comparison with control subjects. FasL was expressed in PBMCs only in Stevens-Johnson syndrome and toxic epidermal necrolysis. A high association between cytotoxic markers and disease severity was seen (P < .001). Conclusions. Our data show that TNF-α, perforin, GrB, and FasL are increased in the early stage of disease, suggesting that a cytotoxic mechanism might be taking part. These findings support the role of T cells in allergic drug reactions and provide further clues pertaining to therapeutic interventions.
Política de acceso abierto tomada de:https://v2.sherpa.ac.uk/id/publication/3193
Keywords: Alergia a los medicamentos; Dermatitis medicamentosa; Fas-L; Drugs; Allergy; Perforin; Granzyme B